Pancasila dan Pendidikan Agama Islam sebagai Dasar Etika: Menjamin Keadilan dan Kepastian Hukum dalam Hukum Bisnis Melalui Islamic Sociological Jurisprudence Theory: Pancasila and Islamic Religious Education as a Basis for Ethics: Ensuring Justice and Legal Certainty in Business Law Through Islamic Sociological Jurisprudence Theory - Muhamad Febrian; Ridwan Alvin Saputra; Muhamad Nafiudin Al Hasani; Ahmad Muhamad Mustain Nasoha (LITERA: Jurnal Ilmiah Mutidisiplin, 2026)
This study aims to examine the role of Pancasila and Islamic Religious Education as ethical foundations in ensuring justice and legal certainty in business law through the perspective of Islamic Sociological Jurisprudence Theory. Pancasila, as the ideological foundation of the Indonesian state, functions not only as a formal source of law but also as a moral and ethical guideline in social and legal life. In the context of Indonesia as a pluralistic society with a Muslim majority, the integration of Islamic law values and national law becomes both a necessity and a challenge.Using a socio-juridical approach, this study highlights how the core values of Pancasila—such as social justice, humanity, and unity—can serve as a foundation for harmonizing Islamic law and national law. The findings indicate that despite the fundamental differences between Islamic law, which is normative-theological in nature, and national law, which tends to be secular, the values of Pancasila are capable of bridging both systems in an inclusive and dialogical manner.Furthermore, the application of Islamic Sociological Jurisprudence Theory enables the development of a legal system that not only emphasizes legal certainty but also reflects substantive justice and religious ethical values. This study recommends strengthening Pancasila-based legal education integrated with Islamic values to create a more adaptive, just, and socially oriented business law system that aligns with the welfare of society.